RUPTURING DIGITAL CHILDHOODS AND PARENTING IN AUSTRALIA? SOCIAL MEDIA BANS, PRIVACY, SCREEN TIME, AND GENERATIVE AI - Leaver, Tama; Third, Amanda; Langton, Katrin; Mannell, Kate; Srdarov, Suzanne (AoIR Selected Papers of Internet Research, 2026)
In the current state of global political, environmental and social challenges, it is perhaps unsurprising that digital childhoods and parenting are in continuous flux as well, with families of all configurations experiencing digital and cultural ruptures. In Australia this discontent with the digital world has led to unprecedented legislation banning all children under the age of 16 from having accounts on social media platforms from December 2025. Despite being popular with the broader public, mental health advocates and most academic research suggest the ban is more likely to do harm than good for Australian children’s health and wellbeing. Paper 1 focuses on this rupture to Australian children’s digital lives. Parents are also conflicted in attempting to balance the young children’s privacy with the connectivity and support that may come in sharing images or stories that includes young people’s photos and data. Paper 2 focuses on these privacy ruptures. Despite being widely seen as outdated in scholarly circles, the focus on screen time, measuring children’s time before a screen without context or questioning the quality of the experience, continues to be a dominant idea Australian families wrestle with. Paper 3 focuses on the ruptures that screen time as a concept continues to bring to families and parenting in particular. And now Generative AI tools present new challenges as they are integrated widely into new and existing platforms and apps without concurrent programs to raise users’ literacy as families and children are increasingly using these tools. The way Generative AI ‘imagines’ children, families and Australianess is the focus of paper 4. These Australian examples speak to similar concerns globally, with parents and children around the world wrestling similar issues, contextualized locally. Other national governments are similarly considering social media bans for children, and thus watching the Australian experiences with implementing the ban, and attempting to enforce age verification, with great interest. This panel presents four papers which explore these ruptures in the Australian context, but with clear global implications.